The Role of Human Resource Analytics in Enhancing Evidence-Based Decision Making in Modern Organizations - Muhammad Bayu; Berlianingsih Kusumawati; Ruhyat Azhari; Roosganda Elizabeth; Ade Suhara (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In the contemporary business landscape, organizations face unprecedented challenges that demand agile, data-driven decision-making processes. Human Resource Analytics (HRA) has emerged as a vital tool to enhance Evidence-Based Decision Making (EBDM) by leveraging workforce data to optimize talent management, employee performance, and organizational outcomes. This study systematically reviews empirical literature (2013–2024) and analyzes case studies to identify key HRA applications, including predictive analytics for workforce planning, employee engagement metrics, and diversity and inclusion analytics. Findings indicate that effective integration of HRA improves accuracy in talent acquisition, retention, and leadership development strategies, contributing to sustained competitive advantage. Nevertheless, barriers such as data privacy concerns, lack of analytics skills, and organizational resistance may limit successful implementation. The study underscores the importance of investing in advanced analytics capabilities, fostering a data-driven culture, and implementing ethical data governance to maximize HRA benefits, providing practical insights for HR practitioners and advancing the discourse on digital transformation in human resources.